KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII PADA PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH [THE CRITICAL THINKING ABILITIES OF GRADE 8 MATHEMATICS STUDENTS USING THE PROBLEM-BASED LEARNING MODEL] - Simatupang, Taruli; Appulembang, Oce (JOHME: Journal of Holistic Mathematics Education, 2022)
Based on PISA research, Indonesian students' mathematical abilities are still below average with one of the assessment indicators being critical thinking skills. This was also found by the authors at the observed schools. The average percentage of students' critical thinking skills in grade 8 is 36% or at less intervals. Meanwhile, the problem-based learning model (PBM) is seen as effective in helping students' critical thinking skills. Thus, the purpose of this study is to describe the critical thinking skills of grade 8 students using the problem-based learning model. The research method used is descriptive qualitative. The conclusion of this paper shows that students' critical thinking skills using the PBM model have an average percentage of 65% for the three indicators. The characteristics of PBM by providing contextual problems can train students' critical thinking power. The stages in PBM make students actively involved in learning by asking various questions as well as in group discussions in designing problem solving. In Christian education, students' critical thinking skills are trained to be able to understand God's truth. Through this, students are expected to live responsibly. Suggestions that can be given are to train students' critical thinking skills in schools through appropriate learning models or approaches. In the implementation of PBM, it is better to pay attention to the estimated time in each stage.BAHASA INDONESIA ABSTRAK: Berdasarkan penelitian PISA, kemampuan matematika siswa Indonesia masih di bawah rata-rata dengan salah satu indikator penilaiannya ialah kemampuan berpikir kritis. Hal ini juga ditemukan oleh penulis di sekolah yang diobservasi. Persentase rata-rata kemampuan berpikir kritis siswa kelas VIII ialah 36% atau pada interval kurang. Sementara itu, model pembelajaran berbasis masalah (PBM) ditinjau efektif dalam membantu kemampuan berpikir kritis siswa. Sehingga, tujuan penelitian ini ialah untuk memaparkan kemampuan berpikir kritis siswa kelas VIII melalui model pembelajaran berbasis masalah. Metode penelitian yang digunakan adalah kualitatif deskriptif. Kesimpulan penulisan ini menunjukkan bahwa kemampuan berpikir kritis siswa melalui model PBM memiliki persentase rata-rata untuk ketiga indikatornya sebesar 65%. Karakteristik PBM dengan pemberian masalah kontekstual dapat melatih daya pikir kritis siswa. Tahapan dalam PBM membuat siswa terlibat aktif dalam pembelajaran dengan mengajukan berbagai pertanyaan juga dalam diskusi kelompok dalam merancang penyelesaian masalah. Dalam pendidikan Kristen, kemampuan berpikir kritis siswa dilatih untuk dapat memahami kebenaran Allah. Melalui hal tersebut, siswa diharapkan hidup bertanggung jawab. Saran yang dapat diberikan adalah melatih kemampuan berpikir kritis siswa di sekolah melalui model atau pendekatan pembelajaran yang sesuai. Dalam pelaksanaan PBM, sebaiknya memperhatikan estimasi waktu dalam setiap tahapannya.